Visible-Light Photocatalytic H2 Production Activity of β-Ni(OH)2-Modified CdS Mesoporous Nanoheterojunction Networks - Vamvasakis, Ioannis; Papadas, Ioannis T.; Tzanoudakis, Theocharis; Drivas, Charalampos; Choulis, Stelios A.; Kennou, Stella; Armatas, Gerasimos S. (My University, 2018)
Photocatalytic water splitting for hydrogen production is an emerging and promising strategy for converting solar energy into chemical fuels. To that end, the development of robust and highly active semiconductor materials is of eminent importance in this field. Here, we demonstrate high-surface-area mesoporous networks comprising interconnected β-Ni(OH)2 modified CdS nanocrystals (NCs) as highly active and stable photocatalysts for hydrogen generation. Compared to single-component CdS assemblies, Ni-modified materials present a strong enhancement of photocatalytic performance for hydrogen evolution under visible light irradiation (λ ≥ 420 nm). By controlling the formation of β-Ni(OH)2 species, the mesoporous β-Ni(OH)2/CdS heterojunction networks at a 10 wt % Ni content reached an outstanding photocatalytic H2-evolution rate of 1.4 mmol h-1 at 20 °C (or ∼35 mmol g-1 h-1 mass activity), associated with an apparent quantum yield (QY) of 72% at 420 nm in a 5 M NaOH aqueous solution containing 10% v/v ethanol as sacrificial reagent. Mechanistic study with UV-vis/near-infrared, photoluminescence, and electrochemical impedance spectroscopy and photocatalytic performance evaluation reveals that the improved photocatalytic performance arises from the strong electronic coupling and charge-transferred states at the p-n β-Ni(OH)2/CdS heterojunctions. These β-Ni(OH)2 modified CdS mesoporous assemblies have important implications for renewable hydrogen generation technologies.
Keywords: Cadmium sulfide; Heterojunctions; Light; Mesoporous materials; Nickel compounds; Hydrogen production